2006
DOI: 10.1016/j.molimm.2005.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Insights into hemolytic uremic syndrome: Segregation of three independent predisposition factors in a large, multiple affected pedigree

Abstract: Mutations in the complement regulators factor H, membrane cofactor protein (MCP), and factor I are associated with atypical hemolytic uremic syndrome (aHUS, MIM 235400), suggesting that the disease develops as a consequence of the inefficient protection of the renal endothelium from damage by the complement system. Incomplete penetrance of the disease in individuals carrying these mutations is, however, relatively frequent. Here, we report the identification of a large, multiple affected aHUS pedigree in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 21 publications
4
105
1
4
Order By: Relevance
“…The following mutations analyzed in this study have been previously reported in aHUS patients: C25F, P32A, N133S, H165R [32], W127x, L289x (c.893delC) [8], A222G, R299W, W468x (c.1446-1450 delTTCAC), D501N [4], R456x, W528x [7] and T520x (c.1610insAT) [31]. The M120V mutation was identified in a Caucasian patient from Saudi Arabia.…”
Section: Mutations Identified In Cfi In Ahus Patientsmentioning
confidence: 80%
See 3 more Smart Citations
“…The following mutations analyzed in this study have been previously reported in aHUS patients: C25F, P32A, N133S, H165R [32], W127x, L289x (c.893delC) [8], A222G, R299W, W468x (c.1446-1450 delTTCAC), D501N [4], R456x, W528x [7] and T520x (c.1610insAT) [31]. The M120V mutation was identified in a Caucasian patient from Saudi Arabia.…”
Section: Mutations Identified In Cfi In Ahus Patientsmentioning
confidence: 80%
“…In this study, we have investigated the functional effects of 14 CFI mutations identified in aHUS patients [4,7,8,31,32]. These mutations are present in different domains: the FIMAC, CD5, LDLr1, region of unknown homology and SP domain (Fig.…”
Section: Mutations In Cfi Ahus Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the general consensus is that mutations of complement regulators more predispose rather than cause the thrombotic microangiopathy (Esparza-Gordillo et al, 2006;Goodship et al, 2004). In this setting, endothelial activation that occurs secondary to injury is undesirably enhanced by excessive complement activation.…”
Section: Discussionmentioning
confidence: 99%